2022
DOI: 10.3390/curroncol29030145
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Real-World Alternative Dosing Strategies of Palbociclib on Progression-Free Survival in Patients with Metastatic Breast Cancer

Abstract: Background: Palbociclib, a cyclin-dependent kinase 4 and 6 (CDK 4/6) inhibitor, in combination with letrozole or fulvestrant has been demonstrated to prolong the progression-free survival (PFS) in patients with hormone receptor-positive (HR+), human epidermal growth factor 2-negative (HER2-) metastatic breast cancer. In efforts to mitigate neutropenic toxicities, oncologists in real-world practice have prescribed alternative dosing strategies with palbociclib, yet the implication on PFS is unknown. Methods: We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Generally, data from real-world experiences have confirmed palbociclib's effectiveness and tolerability in various unselected populations [10]. Frequencies of toxicity seem comparable, however, there seems to be a difference between the clinical trials and real-world setting in how episodes of neutropenia are managed [2,8,22]. For instance, a study in the Netherlands showed that more cycle delays, less dose reductions, and less dose interruptions occurred in clinical practice compared with PALOMA-3 [2].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Generally, data from real-world experiences have confirmed palbociclib's effectiveness and tolerability in various unselected populations [10]. Frequencies of toxicity seem comparable, however, there seems to be a difference between the clinical trials and real-world setting in how episodes of neutropenia are managed [2,8,22]. For instance, a study in the Netherlands showed that more cycle delays, less dose reductions, and less dose interruptions occurred in clinical practice compared with PALOMA-3 [2].…”
Section: Introductionmentioning
confidence: 98%
“…For instance, a study in the Netherlands showed that more cycle delays, less dose reductions, and less dose interruptions occurred in clinical practice compared with PALOMA-3 [2]. From a pharmacokinetic perspective the exposure to palbociclib over time differs between aforementioned treatment modification strategies and, although evidence is inconclusive [8,12,15,22], it is not inconceivable that this might impact effectiveness.…”
Section: Introductionmentioning
confidence: 99%